Building A Multicultural Indonesian Nation Through The Mediation Of Self-Identity And Self-Concept - Dwi Mariyono; Maskuri Maskuri (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The combination of cultural frameworks presented by multicultural identity has many advantages in facilitating adaptation. How can someone feel friendly and comfortable with their environment wherever and whenever an individual is. This persistence seems to describe and treat the world as a "friendly global village". New identities and topics of how individuals deal with internal cultural diversity need to be adequately explored. The fact that there is self-identity and self-concept in society will generally change when influenced by social change. Focusing on examining integrative approaches in Islamic and cultural studies, with the type of library research in the area of descriptive analysis as a way of collecting data, compiling, classifying for analysis and interpretation, it can be concluded that: 1) The need to search for deeper meanings in differences between groups and individual, intra similarity such as behavior, knowledge, emotion, interaction and style; 2) Self-identity is not only a matter of self-description but also a matter of the social labels affixed to it; 3) Rejected social identity results in defensive anticipatory reactions; 4) The self-concept will be awakened, when the need for acknowledgment of the suitability of their identity is also given. The four things above, in its realization there are at least three dimensions as mediation in building the multicultural nation of Indonesia, namely: 1) Mediation of social tolerance; 2) Mediation of religious moderation; 3) Prejudice reduction mediation and 4). Friendly social media mediation